PENGARUH PERUBAHAN SUKU BUNGA TERHADAP NILAI POLIS ASURANSI PENDIDIKAN - VIDYARA VRAJESHVARI, I GUSTI AYU; WIDANA, I NYOMAN; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika, 2024)
Education insurance is an insurance product that provides financial protection for the continuity of a child's education. It offers certainty in funding a child's education. This research utilizes secondary data from the Mortality Table Indonesia IV 2019 and illustration data from an educational insurance policy offered by an insurance company. The data analysis method involves the use of Python programming language, and the steps include determining the Mortality Table for joint life insurance, creating a model to calculate the annual premium and policy value based on the contract specified in the policy, developing software to calculate the premium and policy value using the generated model, and determining the premium and policy value using the software. The aim of this research is to determine   the effect of changes in interest rate on the volicy value . Based on the case study and using the developed software, it is found that the premium price and policy value of education insurance will change when the interest rates change. The premium price will decrease, and the policy value will be smaller when the interest rates increase.